2004
DOI: 10.1111/j.1532-5415.2004.52257.x
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Kyphosis and Ventilatory Dysfunction in Unselected Older Persons: An Epidemiological Study in Dicomano, Italy

Abstract: OBJECTIVES:To assess whether kyphosis is associated with ventilatory dysfunction in older community dwellers. DESIGN: Cross-sectional study. SETTING: The unselected population of Dicomano, Italy aged !65 years. PARTICIPANTS: A total of 323 nonheart failure participants underwent clinical evaluation for the presence of kyphosis and spirometry. The severity of kyphosis was estimated from the difference between standing stature and knee-height-derived stature and from the occiput-wall distance. MEASUREMENTS: Forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 31 publications
3
63
0
2
Order By: Relevance
“…Although it cannot substitute highly accurate clinical measures of kyphosis such as Cobb's angle, OWD has been extensively used in epidemiological studies. It has been associated with depressed mood, postural instability, muscle weakness and disability in older women (2), and may account for a large percentage of the dyspnea and restrictive/ obstructive respiratory dysfunction that often remains unexplained in older persons (3). In the Rancho-Bernardo study, OWD was found to be inversely related to several measures of physical performance, but it was not clear whether osteoporosis mediated this relationship to some extent (4).…”
Section: Introductionmentioning
confidence: 99%
“…Although it cannot substitute highly accurate clinical measures of kyphosis such as Cobb's angle, OWD has been extensively used in epidemiological studies. It has been associated with depressed mood, postural instability, muscle weakness and disability in older women (2), and may account for a large percentage of the dyspnea and restrictive/ obstructive respiratory dysfunction that often remains unexplained in older persons (3). In the Rancho-Bernardo study, OWD was found to be inversely related to several measures of physical performance, but it was not clear whether osteoporosis mediated this relationship to some extent (4).…”
Section: Introductionmentioning
confidence: 99%
“…Postural back pain and/or low back pain, diminished physical performance, impaired respiratory function, and low quality of life arise as a result of kyphotic posture (7)(8)(9)(10)(11). Moreover, increased thoracic kyphosis has a negative effect on postural stability.…”
Section: Introductionmentioning
confidence: 99%
“…Vertebral fractures decrease the pulmonary capacity of these patients, [27][28][29] in whom pulmonary disorders are the most common cause of death. [30][31][32][33] This underlines the importance of identifying any osteonecrosis in patients with severe vertebral collapses.…”
Section: Discussionmentioning
confidence: 99%